The politics of fear the shameless normalization of far-right discourse - Wodak, Ruth 1950- (SAGE, 2021)
The Politics of Fear traces the trajectory of far-right politics from the margins of the political landscape to its very center. It explores the social and historical mechanisms at play, and expertly ties these to the "micro-politics" of far-right language and discourse
Keywords: Conservatism; Discourse analysis; Political parties; Rhetorik; Diskursanalyse; Rechtspopulismus